1993
DOI: 10.3382/ps.0722294
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Distribution of the Protein Content of Samples of Corn, Meat and Bone Meal, and Soybean Meal

Abstract: This study examines the critical assumption of a normal distribution for protein content in feedstuffs. Data were collected from broiler feed mills on the nutrient content of corn, meat and bone meal, and soybean meal. Tests of normality for protein within each feedstuff were performed by each of two methods: 1) the Shapiro-Wilk test (n < 50) or Kolmogorov-Smirnov test (n > 50); and 2) the D'Agostino-Pearson K2 test. Results indicate that protein is non-normally distributed in corn and in meat and bone meal, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The variation in meat and bone meal composition is mainly due to the composition of the raw material source used for production (Donkoh et al, 1994a;Johnson and Parsons, 1997). Kirby et al (1993) examined the assumption of a normal distribution for protein content in feedstuffs by collecting data on the nutrient content of meat and bone meals from broiler feed mills. Statistical analyses of 264 meals showed that the protein content of meat and bone meal was non-normally distributed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The variation in meat and bone meal composition is mainly due to the composition of the raw material source used for production (Donkoh et al, 1994a;Johnson and Parsons, 1997). Kirby et al (1993) examined the assumption of a normal distribution for protein content in feedstuffs by collecting data on the nutrient content of meat and bone meals from broiler feed mills. Statistical analyses of 264 meals showed that the protein content of meat and bone meal was non-normally distributed.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analyses of the results in the present study showed that the protein content of New Zealand meat and bone meals was normally distributed (Kolmogorov-Smirnov normality test, p>0.15; skewness 0.14; kurtosis 0.75). The reason for this may be because the samples obtained by Kirby et al (1993) were from only four broiler feed mills. These samples may not have been representative of the population of meat and bone meals produced as renderers may only sell meals that fall within a specified range to feed mills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation